El crimen y los procesos de los Sucesos de Casas Viejas. Los campesinos y la insidia política - José Luis Gutiérrez Molina (Cahiers de Civilisation Espagnole Contemporaine)
The massacre of January 1933 in Casas Viejas had at the time great social and political repercussions. Even today it is a recurring theme in the history of the thirties of last century in Spain. Both at the time and after, the protagonists, victims, were relegates to the background, because of the political consequences and because they were sees as people without political consciousness. The text shows this vision through the trial proceedings that led to 26 peasants before a military court in June 1934, in particular the allegations of the lawyer who, despite withdrawnness, maintained the idea of a secondary role of the anarchists.